x-6=x-6
0=0
there's infinately many solutions
2007-04-15 10:03:11
·
answer #1
·
answered by twoxoneminusone 2
·
0⤊
0⤋
ing 2x + 4(3x + -6) = 4 + -1(6x + 2) Reorder the terms: 2x + 4(-6 + 3x) = 4 + -1(6x + 2) 2x + (-6 * 4 + 3x * 4) = 4 + -1(6x + 2) 2x + (-24 + 12x) = 4 + -1(6x + 2) Reorder the terms: -24 + 2x + 12x = 4 + -1(6x + 2) Combine like terms: 2x + 12x = 14x -24 + 14x = 4 + -1(6x + 2) Reorder the terms: -24 + 14x = 4 + -1(2 + 6x) -24 + 14x = 4 + (2 * -1 + 6x * -1) -24 + 14x = 4 + (-2 + -6x) Combine like terms: 4 + -2 = 2 -24 + 14x = 2 + -6x Solving -24 + 14x = 2 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -24 + 14x + 6x = 2 + -6x + 6x Combine like terms: 14x + 6x = 20x -24 + 20x = 2 + -6x + 6x Combine like terms: -6x + 6x = 0 -24 + 20x = 2 + 0 -24 + 20x = 2 Add '24' to each side of the equation. -24 + 24 + 20x = 2 + 24 Combine like terms: -24 + 24 = 0 0 + 20x = 2 + 24 20x = 2 + 24 Combine like terms: 2 + 24 = 26 20x = 26 Divide each side by '20'. x = 1.3 Simplifying x = 1.3
2016-05-20 23:32:29
·
answer #2
·
answered by ? 3
·
0⤊
0⤋
the "6 times a number thing" a good rule of thumb is that "is" is "=" so 6 times a number IS (equals) 14 more than that number
the first one, do the distributive property first
3x - 6 - 2x = x - 6
put the x's together
x - 6 = x - 6
put the numbers to one side
x = x therefore, since you have no more numbers, all you are left with is x = x (or 6 = 6 if you did it the other way) it is considered an identity.
2007-04-15 10:02:18
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Question 1
3x - 6 - 2x = x - 6
x - 6 = x - 6
An identity
Question 2
6x = x + 14
or 6x - 14 = x
ie 6 times the number minus 14 gives the number.
2007-04-15 10:14:39
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
Distribut
3x-6-2x=x-6
Combine like terms
x-6=x-6 so this is an identity
if 6x is 14 MORE than x, it needs to be 6x-14=x
2007-04-15 10:01:44
·
answer #5
·
answered by msmthtchr 3
·
0⤊
1⤋
You could try x=-2.8, which works with 3(x-2)-2x=x-6 and it also works with 6x+14=x.
Or x=2.8 if you want 6x=x+14.
Hope this helps.
2007-04-15 10:17:39
·
answer #6
·
answered by serialcoyote 4
·
0⤊
0⤋
It depends on what the question asks... but if you solve, it will be:
3(x-2)-2x=x-6
3x-6-2x=x-6
x-6=x-6
meaning there are infinite solutions.
2007-04-15 10:01:45
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
3x-6-2x=x-6
x-x=0
X can be any number at all, as subtracting it from itself would always produce 0
2007-04-15 10:01:39
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
x can equal any number
2007-04-15 10:05:24
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋